A Politeness Strategies Used by Indonesian Journalists on Racism Issue - Ade Mulaiawan; Suswanto Ismadi Megah; Nurul Aimi Razali (International Journal of English Linguistics, Literature, and Education (IJELLE), 2021)
This study analyzes politeness strategies of the journalists on racism issue of Papuans. This study used Politeness strategies of Brown and Levinson, mainly bold on record and off record strategies to identify the journalists’ politeness. This study employed descriptive – qualitative method to find out politeness of the journalists to report the issue of racism. The data were got from five articles in the Jakarta Post English Newspaper published in Jakarta.  The findings are 33 frequencies which consist of Off record with 20 frequencies (60.6%) and Bald on record with 13 frequencies (39.4%). Each frequency above comes from the amount of the cooperation of data between Off record and Bald on record. The mostly strategy used is “give hints” because the journalists wanted to state his wishes about the racism in Papua. This study can be concluded that these articles the journalists have many understand about the racism and do face to face to the interviewee in order to get much information.Keywords: Politeness, Racism, and Indonesian Journalists